Enhancement of autonomic and psychomotor arousal by exposures to blue wavelength light: importance of both absolute and relative contents of melanopic component. Issue 1 (December 2017) - Yuda, Emi; Ogasawara, Hiroki; Yoshida, Yutaka; Hayano, Junichiro
Abstract Background Blue light containing rich melanopsin-stimulating (melanopic) component has been reported to enhance arousal level, but it is unclear whether the determinant of the effects is the absolute or relative content of melanopic component. We compared the autonomic and psychomotor arousal effects of melanopic-enriched blue light of organic light-emitting diode (OLED) with those of OLED lights with lesser absolute amount of melanopic component (green light) and with greater absolute but lesser relative content (white light). Methods Using a ceiling light consisting of 120 panels (55 × 55 mm square) of OLED modules with adjustable color and brightness, we examined the effects of blue, green, and white lights (melanopic photon flux densities, 0.23, 0.14, and 0.38 μmol/m2 /s and its relative content ratios, 72, 17, and 14%, respectively) on heart rate variability (HRV) during exposures and on the performance of psychomotor vigilance test (PVT) after exposures in ten healthy subjects with normal color vision. For each of the three colors, five consecutive 10-min sessions of light exposures were performed in the supine position, interleaved by four 10-min intervals during which 5-min PVT was performed under usual fluorescent light in sitting position. Low-frequency (LF, 0.04–0.15 Hz) and high-frequency (HF, 0.15–0.40 Hz) power and LF-to-HF ratio (LF/HF) of HRV during light exposures and reaction time (RT) and minor lapse (RT >500 ms) of PVT were analyzed. Results Heart rate was higher and the HF power reflecting autonomic resting was lower during exposures to the blue light than the green and white lights, while LF/HF did not differ significantly. Also, the number of minor lapse and the variation of reaction time reflecting decreased vigilance were lower after exposures to the blue light than the green light. Conclusions The effects of blue OLED light for maintaining autonomic and psychomotor arousal levels depend on both absolute and relative contents of melanopic component in the light.